Assessing Origins of End‐Triassic Tholeiites From Eastern North America Using Hafnium Isotopes. (19th June 2020) - Elkins, Lynne J.; Meyzen, Christine M.; Callegaro, Sara; Marzoli, Andrea; Bizimis, Michael
Abstract: The driving processes responsible for producing the Central Atlantic Magmatic Province, the Large Igneous Province associated with end‐Triassic rifting of Pangea, remain largely debated. Because their compositions encompass most of the Central Atlantic basalt spectrum, tholeiites from southern Eastern North America are considered pivotal for identifying magma origins. New 176 Hf/ 177 Hf measurements for 201 Ma Eastern North American tholeiites dominantly record a local petrogenetic history. Their εHf ratios, corrected to an emplacement age of 201 Ma (−7.85 to +5.86), form a positive but shallowly sloped array slightly deviating from the terrestrial array on a εHf versus εNd diagram. Comparison of 176 Hf/ 177 Hf to other isotope ratios and trace elements helps to rule out several petrogenetic scenarios, particularly mixing of melts from global depleted or enriched mantle components. In contrast, partial melting of subduction‐metasomatized mantle can explain the parental magma composition for southern Eastern North America. Such metasomatism likely occurred during Paleozoic subduction around Pangea and may have been dominated by sediment‐derived fluid reactions. The observed 176 Hf/ 177 Hf versus 143 Nd/ 144 Nd array may reflect subsequent assimilation of lower continental crust, perhaps together with limited direct melting of recycled continental crust in the asthenosphere. The proposed recycling scenario does not specifically support or preclude a mantle plume origin for the Central Atlantic Magmatic Province but instead points toward the presence of a distinct local mantle source and crustal assimilation processes during magma transport. Detailed understanding of these local effects is needed in order to more accurately understand the origins of Large Igneous Provinces. Key Points: End‐Triassic tholeiites from Eastern North America were likely products of melting Paleozoic age, subduction‐metasomatized mantle Direct melting of recycled crustal rocks may also have occurred but cannot fully explain the tholeiite isotopic compositions observed Southern Eastern North American tholeiites likely also experienced assimilation of lower continental crust, possibly intermediate granulite